2000
DOI: 10.1021/bi001113y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Escherichia coli Replicative Helicase PriA Protein with Single-Stranded DNA

Abstract: Quantitative analyses of the interactions of the Escherichia coli replicative helicase PriA protein with a single-stranded DNA have been performed, using the thermodynamically rigorous fluorescence titration technique. The analysis of the PriA helicase interactions with nonfluorescent, unmodified nucleic acids has been performed, using the macromolecular competition titration (MCT) method. Thermodynamic studies of the PriA helicase binding to ssDNA oligomers, as well as competition studies, show that independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
247
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 40 publications
(254 citation statements)
references
References 48 publications
5
247
2
Order By: Relevance
“…Although there are no cooperative interactions between the PriA helicase bound in the gap complex and to the dsDNA of the gapped DNA substrates, the increase of [NaCl] (20,21). In the case of the gap complex, low ADP or ATP␥S concentrations only slightly affect ⌬F 1 , ⌬F 2 , and ⌬F 3 , as compared with the same parameters determined in the absence of the cofactors, indicating similar structures of the formed complexes (Tables 1 and 2).…”
Section: The Minimum Site Size Of the Pria-gapped Dna Substrate Complmentioning
confidence: 61%
See 2 more Smart Citations
“…Although there are no cooperative interactions between the PriA helicase bound in the gap complex and to the dsDNA of the gapped DNA substrates, the increase of [NaCl] (20,21). In the case of the gap complex, low ADP or ATP␥S concentrations only slightly affect ⌬F 1 , ⌬F 2 , and ⌬F 3 , as compared with the same parameters determined in the absence of the cofactors, indicating similar structures of the formed complexes (Tables 1 and 2).…”
Section: The Minimum Site Size Of the Pria-gapped Dna Substrate Complmentioning
confidence: 61%
“…The slope of the log-log plot, ∂logK G / ∂log[NaCl] ϭ Ϫ6.1 Ϯ 0.7, whereas the analogous slopes, obtained for the ssDNA 10-mer and 18-mer, respectively, engaging only the strong DNA-binding subsite, are ∂logK 10 / ∂log[NaCl] ϭ Ϫ2.5 Ϯ 0.4 and ∂logK 18 /∂log[NaCl] ϭ Ϫ3.0 Ϯ 0.5, respectively (21). Clearly, the net number of ions released, ϳ6, in the formation of the gap complex is even larger than the number of the nucleotides in the ssDNA gap.…”
Section: The Minimum Site Size Of the Pria-gapped Dna Substrate Complmentioning
confidence: 97%
See 1 more Smart Citation
“…In this context, the PriA protein has very different stoichiometries and affinities for single-stranded DNA (ssDNA) and dsDNA conformations. [19][20][21][22][23][24] While the site size of the protein on ssDNA is ∼ 20 nucleotides, the site size of the PriA-dsDNA complex is only ∼5 bp. Moreover, the affinity for dsDNA is ∼1-2 orders of magnitude higher than the affinity for ssDNA.…”
Section: Binding Of Pria Protein To the Pas Substratementioning
confidence: 99%
“…The presence of different conformational states during each NTPase cycle has been observed in most established helicases, although the detailed mechanism can vary. For example, the helicase DnaB exhibits 210-fold greater affinity for ssDNA upon NTP binding (51), whereas nucleotide binding reduced the affinity of PriA for ssDNA about 5-fold (43). Structural studies of SF1 helicases have shown that nucleotide binding induces the close up of the cleft between 1A and 2A domains (52)(53)(54).…”
Section: Contribution Of Recd-like Domain I To the Processivity Of Traimentioning
confidence: 99%